Predictive Roles of Gender, Self-Efficacy, and Work Experience on Job Burnout among Selected Basic School Teachers in Ogbomoso Metropolis - Ajao, Paul Oluwatosin; Oguntayo, Rotimi; Ajao, Tunmise Seun; Adeyi, Margaret Abiola (Journal of Social and Scientific Education, 2025)
Job burnout is one of the most serious workplace challenges. Meanwhile, studies focusing on the interplay between socio-demographics, self-efficacy, and job burnout are insufficient, particularly in Nigeria. This study aimed to examine whether self-efficacy, gender, and work experience determine job burnout among school teachers in Ogbomoso, Oyo State, Nigeria. A Cross-sectional design was employed, utilizing questionnaires for data collection. A multistage sampling and convenience sampling technique was used to sample 1,725 teachers in 102 selected schools across the five local government areas of Ogbomoso. Data were collected using the Teachers’ Self-Efficacy Scale and the Maslach Burnout Inventory—Teachers' Survey (MBI-ES). The analysis showed no significant gender difference in job burnout among the selected teachers in Ogbomoso metropolis. However, a significant difference was found in job burnout based on years of work experience F(2,1723) = 6.234 p<.05), with teachers in the 1–7 year category exhibiting significantly higher burnout scores than other groups. Self-efficacy was found to significantly and negatively predict job burnout among the selected teachers(R= -.479, R2 =.576 F=14.573; p <.05). The study concludes that higher levels of self-efficacy are associated with lower levels of job burnout among school teachers. Teachers with 1–7 years of work experience are particularly susceptible to higher burnout levels. Recognizing the negative predictive role of self-efficacy on job burnout, interventions aimed at enhancing self-efficacy are recommended to mitigate burnout risks. The research recommends that policy makers should prioritize new teachers’ self-efficacy training to reduce the job burnout.